2015
DOI: 10.20491/isader.2015215746
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Professional Tour Guides Performances By Local Tourists

Abstract: Özetİnternet ve sosyal ağlar sayesinde daha bilinçli turist profilinin hâkim olduğu bir döneme girilmiştir. Bu durum turizm hizmetlerinin en önemli bileşenlerinden biri olan profesyonel turist rehberliği hizmetlerini de etkilemiştir. Profesyonel turist rehberi (PTR), paket turların başarısını etkileyen en önemli faktörlerden biridir. Bu araştırmanın temel amacı yerli turistler açısından PTR'lerin sahip olması beklenen özelliklerin, önem düzeylerini belirleme ve PTR'lerin sergiledikleri performanslarını ortaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They are the package tours which include at least two of transportation, accommodation and other touristic services that are not considered to be the contributory to them, which are sold with allinclusive prices and which involve at least one overnight stay (Demircan, 2007: 11). When the researches on package tours in the literature are examined, it can be seen that Karamustafa and Çeşmeci (2006) studied the managerial problems faced by tourist guides, Çolakoğlu et al (2009) analyzed the customer complaints in package tours, Olcay et al (2015) examined the performances of professional tourist guides, and Yetiş and Ardış (2018) studied the perceived service quality in regional package tours. In the studies conducted so far, no studies have been found on ethics or ethical principles in package tours.…”
Section: Tourism and Ethicsmentioning
confidence: 99%
“…They are the package tours which include at least two of transportation, accommodation and other touristic services that are not considered to be the contributory to them, which are sold with allinclusive prices and which involve at least one overnight stay (Demircan, 2007: 11). When the researches on package tours in the literature are examined, it can be seen that Karamustafa and Çeşmeci (2006) studied the managerial problems faced by tourist guides, Çolakoğlu et al (2009) analyzed the customer complaints in package tours, Olcay et al (2015) examined the performances of professional tourist guides, and Yetiş and Ardış (2018) studied the perceived service quality in regional package tours. In the studies conducted so far, no studies have been found on ethics or ethical principles in package tours.…”
Section: Tourism and Ethicsmentioning
confidence: 99%